2006
DOI: 10.1176/appi.ajp.163.2.322
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of White Matter Pathology in Bipolar Disorder Adolescents Experiencing Their First Episode of Mania: A Diffusion Tensor Imaging Study

Abstract: These findings suggest that prefrontal white matter abnormalities are present early in bipolar disorder and may consist largely of axonal disorganization. The presence of changes in young first-episode patients also suggests that white matter pathology may represent an early marker of bipolar disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
137
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(158 citation statements)
references
References 15 publications
19
137
0
1
Order By: Relevance
“…One explanation is that lithium may have different generalized effects in healthy and diseased brains. This global white matter increase is also of interest considering recent evidence for white matter pathology as an early marker for bipolar disorder [16] and lithium's effect of causing formation of multiple axons in rat hippocampus neurons through inhibition of glycogen synthase kinase-3β [17].…”
Section: Discussionmentioning
confidence: 99%
“…One explanation is that lithium may have different generalized effects in healthy and diseased brains. This global white matter increase is also of interest considering recent evidence for white matter pathology as an early marker for bipolar disorder [16] and lithium's effect of causing formation of multiple axons in rat hippocampus neurons through inhibition of glycogen synthase kinase-3β [17].…”
Section: Discussionmentioning
confidence: 99%
“…25 Kanaan et al 59 have underlined the controversial use of ROI approaches because of the great variability of WM tracts and the lack of anatomical landmarks to draw them. This methodological shortcoming might explain the rather contradictory findings of DTI studies in BP, reporting predominantly increased ADC or decreased FA in frontal WM [19][20][21] with one study reporting increased as well as decreased FA in different ROIs. 22 The present findings have to be interpreted in light of some limitations.…”
Section: Diffusion Tensor Tractography In Bipolar Patients J Houenou mentioning
confidence: 99%
“…[19][20][21][22] As the amount of FA has been shown to be an indirect measures of the directionality and coherence of fiber tracts, 23,24 DTI studies in BP suggest a loss of coherence in frontal WM bundles. However, these studies have investigated predefined and limited regions of interest (ROIs), representing only a part of a specific WM bundles and might thus be susceptible to overlook subtle differences between study groups.…”
Section: Introductionmentioning
confidence: 99%
“…5,14 Severe white matter abnormalities in patients with bipolar disorder have been usually investigated using magnetic resonance imaging (MRI) studies of white matter volumes and hyperintensities, magnetization transfer studies and MRI spectroscopy. 11,[14][15][16] More recently, diffusion tensor imaging (DTI), an MRI technique that explores the microstructural integrity of white matter, 17 has been applied in studies of bipolar disorder. Overall, the few previous DTI studies reported reduced fractional anisotropy and increased radial diffusion in the frontal and prefrontal lobes, internal capsule, corpus callosum and uncinate fasciculus of patients with bipolar disorder.…”
Section: Introductionmentioning
confidence: 99%